566 Transthyretin and light-chain cardiac amyloidosis: clinical characteristics, echocardiographic findings, and outcomes of a large cohort of patients in Northern Italy. (8th December 2021) - De Angelis, Maria Grazia; Tomasoni, Daniela; Pancaldi, Edoardo; Pezzola, Elisa; Saccani, Nicola; Nardi, Matilde; Cani, Dario Salvatore; Lombardi, Carlo Mario; Metra, Marco
Abstract: Aims: To describe the characteristics of a cohort of patients with cardiac amyloidosis (CA) and to compare the two most common phenotypes of CA, transthyretin (ATTR) and immunoglobulin light-chain (AL). Methods and results: One-hundred and eighty patients [ n  = 115 (64%) men, 74 ± 11 years] were retrospectively included from January 2013 to April 2021 in a single centre in Northern Italy. The majority [ n  = 102 (57%)] had ATTR-CA, whereas 78 patients (43%) had AL-CA. ATTR-CA patients were older (79 ± 7 vs. 66 ± 10 years, P  < 0.001) and with higher prevalence of cardiovascular comorbidities, compared to those with AL-CA. ATTR-CA patients had higher N-terminal pro-B-type natriuretic peptide (Nt-proBNP) and troponin levels, and lower haemoglobin and estimated glomerular filtration rate. Echocardiographic findings suggested a more advanced stage of the disease in the ATTR-CA subgroup [left ventricular ejection fraction (LVEF), 51 ± 10% vs. 60 ± 9%; global longitudinal strain (GLS), −11 ± 3% vs. −13 ± 4%; peak systolic wall motion velocity, 4.9 ± 1.7 vs. 6.4 ± 1.9; left ventricular mass index (LVMI) 316 ± 133 g/m 2 vs. 157 ± 72 g/m 2 ; left atrium volume index (LAVI) 48 ± 17 ml vs. 40 ± 16 ml; right ventricular diameter 31 ± 9 mm vs. 22 ± 5 mm; tricuspidal annular plane systolic excursion (TAPSE) 17 ± 5 vs. 19 ± 5; all P  < 0.05). During a median follow-up of 15 (6–31) months, 68 (38%) patients died. All-cause death occurred in 31% vs. 46% patients with ATTR- and AL-CA, respectively. AL-CA was an independent predictor of mortality (adjusted hazard ratio 2.62, 95% confidence interval 1.55–4.43; P  < 0.001). Other independent predictors of mortality were age, systolic blood pressure, Nt-proBNP, troponin and GLS. When cardiovascular (CV) death was considered, there was no significant difference between the two phenotypes (log rank P  = 0.384). Conclusions: Despite ATTR-CA patients showed worse baseline characteristics, suggesting a more advanced disease at presentation, AL-CA phenotype was associated with a higher risk of all-cause death. Of note, CV mortality was comparable between the two groups.